(untitled) (KULT_online, 2009)
This study by Ulrich Haegele, cultural anthropologist in Tuebingen, explores the historical development of the interaction between photography and ethnography. In the process he detects the following three formative phases: “meaning creation”, “ideologisation”, and “professionalisation”. In addition to a wide-ranging theoretical introduction, which focuses on the history of the field of ethnology (and its dynamic with other fields) as well as various theoretical approaches to the study of visual culture, the monograph distinguishes itself through a painstaking treatment of the “nature” of photography and the essential stages of image creation. The author’s perspective is interdisciplinary throughout and he consistently defines terms with contextual examples. Rounding out the study is a chronological bibliography of ethnographic photography and visual anthropology.